2003
DOI: 10.1097/00063110-200303000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Is a career in emergency medicine associated with stigma?

Abstract: This paper demonstrates that stigmatizing opinions towards emergency medicine exist and that these negative opinions may be widely held by hospital staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Smith, [26] in a study carried out in the Royal Berkshire Hospital in England, reported such a negative attitude. Iranian EPs also reported this problem, especially in private hospitals.…”
Section: Discussionmentioning
confidence: 97%
“…Smith, [26] in a study carried out in the Royal Berkshire Hospital in England, reported such a negative attitude. Iranian EPs also reported this problem, especially in private hospitals.…”
Section: Discussionmentioning
confidence: 97%
“…There have been a number of studies describing factors that influence EM career choice . Kazzi et al .…”
Section: Introductionmentioning
confidence: 99%
“…This included a Medline search and a hand search of the Annals of Emergency Medicine and the Emergency Medicine Journal over the last 5 years. These searches revealed only one relevant study which focused on negative stigma attached to a career in EM, linking this to “professional distancing”, isolation and perceived communication difficulties 8. These findings advocate the need for further studies such as this one in the area of interprofessional relations.…”
Section: Methodsmentioning
confidence: 99%